Developing a training program of knowledge and skills in the context of administrative involuntary hospitalization: a pilot trial - Shiina, Akihiro; Sudo, Yusuke; Suzuki, Yodai; Kamata, Yu; Niitsu, Tomihisa; Fujii, Chiyo (Frontiers in Psychiatry, 2025)
IntroductionTo deal with offenders with mental disorder, the administrative involuntary hospitalization (AIH) scheme was adopted in Japan in 1950. However, its outcomes as well as standard of AIH adaptation remain obscure. Recently we developed a training program for improving the skills for AIH decision-making for early-career psychiatrists. The aim of this pilot study is to implement and investigate the effectiveness of this program.MethodsThrough snowball sampling, this open interventional exploratory pilot study recruited licensed physicians who possessed or intended to acquire a designated psychiatrist license. Eighteen physicians were enrolled and attended a 4 h seminar including group discussion following a self-learning video session. Subsequently, they completed the Mental Health and Welfare Act Administrative Involuntary Hospitalization Test (AIH Test). An unpaired t-test was used for analysis of the AIH Test scores.ResultsIn total, 17 participants (mean age, 35.6 ± 5.5 years) completed the post-seminar questionnaire on the effectiveness of the seminar. The mean ± standard deviation AIH Test score improved from 12.1 ± 2.1 before the seminar to 14.7 ± 3.9 after the seminar (degrees of freedom = 34, t = −2.45, P = 0.019 [two-tailed]), indicating a significant improvement in knowledge of AIH. As a secondary outcome, scores on the Academic Motivation Scale, reflecting the motivation to study forensic psychiatry, did not change significantly before and after the seminar.DiscussionOur AIH skills training program improves knowledge of AIH, without affecting the motivation to study forensic psychiatry.